Ответ:.
Объяснение:Ответ такой :
1. х ³- 2х²-3х -5 = (х²-3х-1)(х-1)+(х-4) (решение на листке бумаге )
2. 2х³ -2х²+х+3 =(х²-3х-4)(2х+4) +(21х+19) (решение на листке )
3.х^5-3х³-+2 = решение на листке
4.6х ^4-2х+3 = решение на листке
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:.
Объяснение:Ответ такой :
1. х ³- 2х²-3х -5 = (х²-3х-1)(х-1)+(х-4) (решение на листке бумаге )
2. 2х³ -2х²+х+3 =(х²-3х-4)(2х+4) +(21х+19) (решение на листке )
3.х^5-3х³-+2 = решение на листке
4.6х ^4-2х+3 = решение на листке